Multiple focal nodular hyperplasia of the liver associated with spinal and pulmonary arteriovenous malformations - Cordeiro, MN (2009)
Focal nodular hyperplasia (FNH) is frequently found incidentally in liver imaging but multiple FNH, especially when associated with systemic vascular malformations, are rare. We report on the case of a patient with lumbar sciatalgia and paraparesis. Spinal magnetic resonance angiography (MRA) showed a spinal cord arteriovenous shunt (SCAVS), its arterial feeders and venous drainage, which were later confirmed by digital subtraction angiography (DSA). MRA of the spine offers promising results in the characterization of SCAVS. Thoracoabdominal CT and MRI revealed multiple hepatic FNH and a pulmonary arteriovenous malformation (AVM). Indeed, this is the first reported case of the rare multiple FNH syndrome associated with a spinal AVM.